Pharmacognosical & Plant tissue culture studies of Achillea millefolium L. - MR Shams Ardekani; A Hadjiakhoondi; AH Jamshidi; P Mohammad Rafiee (Institue of Medicinal Plants, ACECR, 2006)
Background: Achillea millefolium L. is a traditional herbal medicine used widely as a spasmolytic, anti- cancer, anti - inflammatory and carminative. This paper focuses on the analysis of the chemical composition of essential oil from the upper parts of plant and calli of Achillea millefolium L. Methods: Growing the calli of Achillea millefolium L. and production its secondary metabolites studied and compared with those in the whole plant. Achillea seeds were first surface sterilized by shaking in 3% (W/V) aqueous hydrogen peroxide, then by shaking in 5% Na hypochlorite and 80% aqueous - ethanol solution, then under aseptic condition, strile petrydishes containing autoclaved agar (0.8%) and kept in the dark at a temprature of 25-27 oC. Seedlings were developed in two weeks. Then they were transferred to strile Murashing and Skoog (MS) culture media which were containing 2,4-D (3mg/l), IAA (5mg/l) and K (0.2mg/l) as plant grow regulators. The amorph masses (calli) were produced and subcultured every 40-45 days. Results: The result obtained from GC/MS of essential oil of plant indicated that the major compounds of the essential oil are alpha - Pinene, beta - Pinene and Caryophyllene oxide. Conclusion: In contrast, calli lacked essential oil, this was indicated upon GC of its dichlorometanic extract. However phytochemical tests indicated that some tannins were produced by calli.